Work-Life Balance as a Predictor of Performance in Female Workers in the Public Sector in the Digital Era - Dewi Sulfa Saguni; Muhammad Hidayat Djabbari; Fetni Fetni; Mardiana Mardiana; Risman Risman (Publik : (Jurnal Ilmu Administrasi), 2026)
Work-life balance has become an important issue in public sector human resource management, particularly for female employees who simultaneously perform professional and family responsibilities in the era of digital transformation. Increasing digitalization has improved workplace flexibility while also blurring the boundaries between work and personal life, potentially affecting employee performance. This study aims to examine the effect of work-life balance on the performance of female workers in the public sector and to analyze the roles of organizational support, digital capabilities, and family circumstances as contextual variables. A quantitative approach with a correlational design integrated with mixed methods was employed. Quantitative data were collected through questionnaires from 210 female public sector employees and analyzed using Structural Equation Modeling (SEM), while qualitative data from interviews and observations were used to strengthen the interpretation of the findings. The results indicate that work-life balance has a positive and significant effect on employee performance. Organizational support strengthens this relationship as a mediating variable, whereas digital capabilities and family circumstances function as moderating variables. The findings also reveal that work flexibility in the digital era does not automatically improve work-life balance; without supportive organizational policies and adequate digital competencies, it may increase work stress and role conflict. This study concludes that improving the performance of female public sector employees requires an integrated approach through gender-responsive organizational policies, enhanced digital capabilities, flexible work arrangements, and stronger family support. These findings provide practical implications for developing inclusive and sustainable human resource management policies in the digital era